Geospatial Assessment of Geothermal Potential In The Jeffara Plain, Northwest Libya: A Weighted Overlay Analysis Approach - Alkaryani, Belkasem; Saleh, Mohamed; Ibrahem, Abdlsaid; Hamad, Salah (AlQalam Journal of Medical and Applied Sciences, 2026)
The Jeffara Plain in northwest Libya represents a critical frontier for low-enthalpy geothermal energy development within the transboundary Northwest Sahara Aquifer System (NWSAS). This study applies an integrated framework combining remote sensing, Geographic Information Systems (GIS), and Multi-Criteria Decision Analysis (MCDA) to delineate geothermal potential zones. Seven thematic layers magnetic survey, gravity survey, transmissivity, geological setting, aquifer thickness, piezometric surface, and land use were standardized and weighted using the Analytical Hierarchy Process (AHP), then integrated through a Weighted Overlay Analysis (WOA) to derive a Geothermal Potential Index (GPI). The resulting map identifies the Az-Zahra region as the most favorable target, where the Al-Aziziyah geothermal aquifer exhibits temperatures on the order of 50–70 °C at depths of 200–350 m, suitable for direct-use applications such as desalination, greenhouse heating, and low-temperature industrial processes. The spatial correspondence between high-potential classes and existing thermal wells provides qualitative support for the validity of the proposed framework. Comparison with regional North African case studies further suggests that this workflow is transferable and can guide future, more quantitative validation efforts such as Receiver Operating Characteristic Area Under the Curve (ROC–AUC) analysis for sustainable geothermal exploration in arid, data-scarce environments.